Tactile Sensors: High‐Performance Flexible Tactile Sensor Enabling Intelligent Haptic Perception for a Soft Prosthetic Hand (Adv. Mater. Technol. 8/2019). Issue 8 (8th August 2019) - Liang, Ziwei; Cheng, Jiahui; Zhao, Qian; Zhao, Xingwei; Han, Zhiyuan; Chen, Ying; Ma, Yinji; Feng, Xue
Abstract : The ability of tactile perception is essential for intelligent prosthetic hands to perform complex operations and achieve friendly external interaction, but is still a challenge to achieve. In article number1900317, Ziwei Liang, Xue Feng and co‐workers propose a new kind of high‐performance flexible tactile sensor enabling intelligent tactile perception for soft prosthetic hands (SPD). The smart SPD completes various complicated tasks like a real hand. All of these have demonstrated the promising applications of soft prosthetic hands with sense of touch in robotics, artificial limbs and medicine.